Cover Feature: Physico‐Chemical Properties and Principal Component Analysis of Biobased Thermosets Developed with Different Batches of Industrial Humins (ChemPlusChem 7/2022). Issue 7 (24th May 2022) - Dinu, Roxana; Gaysinski, Marc; de Jong, Ed; Mija, Alice
Abstract : The cover image shows the design of sustainable polymers by a green chemistry approach starting from industrial waste or side‐products or from renewable biobased building blocks. By applying the principal component analysis (PCA) on different biorefineries' humins batches, an approach to predict the potential properties of their derived thermosets was developed. To develop new and bio‐based thermoset resins, industrial humins batches were crosslinked with glycerol diglycidyl ether (GDE), an aliphatic epoxy compound derived from bio‐renewable resources. We were able thus to transform and valorize by‐products into materials with tunable properties. In these complex industrial systems, the PCA analysis is a very useful tool to predict the structure‐reactivity‐properties‐application interdependent relationship. This research is done at the Institute of Chemistry of Nice in the group lead by Professor Alice Mija on recyclables, reprocessables and repairables, sustainables and biobased polymers and composites. More information can be found in the Research Article by A. Mija and co‐workers .